Efektivitas Latihan Napas Pagi Dan Malam Terhadap Kesejahteraan Psikologis - Ajeng P, Heimas; H, ,Amelda Haerlina; K, Dian Asmingsih Arun; A, Ghiska Putri Maesa; Susanti, Ruth Natalia (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the effectiveness of morning and evening breathing exercises on the psychological well-being of adults. The research used a quantitative method with a one-group pretest-posttest design. The subjects consisted of five adults from diverse backgrounds, selected using purposive sampling. The intervention involved mindful breathing exercises conducted twice daily for 7 days, with each session lasting 5–10 minutes. The instrument used was the DASS-21 to measure stress, anxiety, and depression, along with daily reflective questions to capture participants’ subjective experiences. Data were analyzed descriptively using both quantitative and qualitative approaches. The results showed that most participants experienced improvements in relaxation, self-worth, and reduced anxiety. Although outcomes varied between individuals, no significant negative effects were observed. The findings suggest that twice-daily breathing exercises have the potential to serve as an effective self-regulation strategy for enhancing psychological well-being. This study recommends incorporating breathing practices as part of non-pharmacological biopsychological interventions for stress management programs.